2016
DOI: 10.1021/acs.jafc.6b03499
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-alkaline Treatment as a Practical Degradation Strategy To Reduce Indospicine Contamination in Camel Meat

Abstract: Ingestion of indospicine-contaminated camel and horse meat has caused fatal liver injury to dogs in Australia, and it is currently not known if such contaminated meat may pose a human health risk upon dietary exposure. To date, indospicine-related research has tended to focus on analytical aspects, with little information on post-harvest management of indospicine-contaminated meat. In this study, indospicine degradation was investigated in both aqueous solution and also contaminated meat, under a range of cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Indospicine hydrolysis directly to 2-aminopimelic acid was also reported with concentrated hydrochloric acid (6 N HCl, 120 °C, 20 h) [ 124 ]. Indospicine was also found to be stable under mild acidic aqueous conditions in vitro and it was hypothesised that the mild acidic conditions in the stomach would not be able to hydrolyse indospicine [ 137 ].…”
Section: Rumen Microbial Detoxification Of Plant Toxinsmentioning
confidence: 99%
“…Indospicine hydrolysis directly to 2-aminopimelic acid was also reported with concentrated hydrochloric acid (6 N HCl, 120 °C, 20 h) [ 124 ]. Indospicine was also found to be stable under mild acidic aqueous conditions in vitro and it was hypothesised that the mild acidic conditions in the stomach would not be able to hydrolyse indospicine [ 137 ].…”
Section: Rumen Microbial Detoxification Of Plant Toxinsmentioning
confidence: 99%
“…A wide range of variation was observed for most of the variables between the four dromedary types, with a clear differentiation of Majaheem from the other three dromedary types (Maghateer, Hamrah and Safrah). The effect of thermo-alkaline treatment in reducing hepatotoxin contamination in camel meat has been demonstrated (Tan et al 2016). Whereas myostatin gene structure, polymorphism and expression in dromedaries have been characterised (Favia et al 2019), no (genome-wide) association study has been performed for growth or meat performance.…”
Section: Meat Performance and Compositionmentioning
confidence: 99%
“…Our results suggest that the human digestive system does not have the capacity to degrade indospicine. Tan et al [ 38 ] have recently reported that microwaving indospicine-contaminated camel meat under mild alkaline conditions (0.05% sodium bicarbonate, pH 8.8, 15 min) achieved 100% degradation of indospicine, with products identified as 2-aminopimelamic acid (major) and 2-aminopimelic acid (minor) ( Figure 5 ). Such processing treatments may have ready applicability in the pet food industry given the recorded sensitivity of dogs to indospicine-contaminated meat, but are perhaps not appropriate in the processing of food for human consumption.…”
Section: Resultsmentioning
confidence: 99%
“…Such processing treatments may have ready applicability in the pet food industry given the recorded sensitivity of dogs to indospicine-contaminated meat, but are perhaps not appropriate in the processing of food for human consumption. Additionally, the metabolic fate and toxicity of indospicine hydrolysis products remains unknown and requires further investigation [ 38 ].…”
Section: Resultsmentioning
confidence: 99%